The Use of Microalgae for Coupling Wastewater Treatment With CO2 Biofixation - Molazadeh, Marziyeh; Ahmadzadeh, Hossein; Pourianfar, Hamid R.; Lyon, Stephen; Rampelotto, Pabulo Henrique (Frontiers in Bioengineering and Biotechnology, 2019)
Production and emission of CO2 from different sources have caused significant changes in the climate, which is the major concern related to global warming. Among other CO2 removal approaches, microalgae can efficiently remove CO2 through the rapid production of algal biomass. In addition, microalgae have the potential to be used in wastewater treatment. Although, wastewater treatment and CO2 removal by microalgae have been studied separately for a long time, there is no detailed information available on combining both processes. In this review article, microalgae-based CO2 biofixation, various microalgae cultivation systems,̄ and microalgae-derived wastewater treatment are separately discussed, followed by the concept of integration of CO2 biofixation process and wastewater treatment. In each section, details of energy efficiency and differences across microalgae species are also given.